Abusive Head Trauma and Mortality–An Analysis From an International Comparative Effectiveness Study of Children With Severe Traumatic Brain Injury. Issue 8 (August 2017) - Miller Ferguson, Nikki; Sarnaik, Ajit; Miles, Darryl; Shafi, Nadeem; Peters, Mark J.; Truemper, Edward; Vavilala, Monica S.; Bell, Michael J.; Wisniewski, Stephen R.; Luther, James F.; Hartman, Adam L.; Kochanek, Patrick M.
Abstract : Objectives: Small series have suggested that outcomes after abusive head trauma are less favorable than after other injury mechanisms. We sought to determine the impact of abusive head trauma on mortality and identify factors that differentiate children with abusive head trauma from those with traumatic brain injury from other mechanisms. Design: First 200 subjects from the Approaches and Decisions in Acute Pediatric Traumatic Brain Injury Trial—a comparative effectiveness study using an observational, cohort study design. Setting: PICUs in tertiary children's hospitals in United States and abroad. Patients: Consecutive children (age < 18 yr) with severe traumatic brain injury (Glasgow Coma Scale ⩽ 8; intracranial pressure monitoring). Interventions: None. Measurements and Main Results: Demographics, injury-related scores, prehospital, and resuscitation events were analyzed. Children were dichotomized based on likelihood of abusive head trauma. A total of 190 children were included ( n = 35 with abusive head trauma). Abusive head trauma subjects were younger (1.87 ± 0.32 vs 9.23 ± 0.39 yr; p < 0.001) and a greater proportion were female (54.3% vs 34.8%; p = 0.032). Abusive head trauma were more likely to 1) be transported from home (60.0% vs 33.5%; p < 0.001), 2) have apnea (34.3% vs 12.3%; p = 0.002), and 3) have seizures (28.6% vs 7.7%; p < 0.001) during prehospital care. Abusive head trauma had a higher prevalence of seizures during resuscitation (31.4 vs 9.7%; p = 0.002). After adjusting for covariates, there was no difference in mortality (abusive head trauma, 25.7% vs nonabusive head trauma, 18.7%; hazard ratio, 1.758; p = 0.60). A similar proportion died due to refractory intracranial hypertension in each group (abusive head trauma, 66.7% vs nonabusive head trauma, 69.0%). Conclusions: In this large, multicenter series, children with abusive head trauma had differences in prehospital and in-hospital secondary injuries which could have therapeutic implications. Unlike other traumatic brain injury populations in children, female predominance was seen in abusive head trauma in our cohort. Similar mortality rates and refractory intracranial pressure deaths suggest that children with severe abusive head trauma may benefit from therapies including invasive monitoring and adherence to evidence-based guidelines. Abstract : Supplemental Digital Content is available in the text.